PENGARUH FRAUD AUDIT TRAINING, SKEPTISISME PROFESIONAL, DAN AUDIT TENURE PADA KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Putri, Kompiang Martina Dinata; Wirama, Dewa Gede; Sudana, I Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.11.TAHUN 2017DO - 10.24843/EEB.2017.v06.i11.p03, 2017)
This study analyses the effect of fraud audit training, professional scepticism, and audit tenure on auditors’ ability to detect fraud. The sample of this study consisted of 42 auditors from public accounting firm in Bali in 2016. Samples are selected using purposive sampling technique. Fraud audit training, professional scepticism, and audit tenure were measured by the use of questionnaires. Data analysis technique used in this research is multiple linear regression. The result showsthat fraud audit training, professional scepticism, and audit tenure have positive effects on auditors’ fraud detection capabilities.